MRP8/ABCC11 Expression Is Regulated by Dexamethasone in Breast Cancer Cells and Is Associated to Progesterone Receptor Status in Breast Tumors - Mylène Honorat; Aurélia Mesnier; Julie Vendrell; Attilio Di Pietro; Valérie Lin; Charles Dumontet; Pascale Cohen; Léa Payen (International Journal of Breast Cancer)
The ATP-binding cassette multidrug resistance protein 8 (MRP8/ABCC11) mediates the excretion of anticancer drugs. ABCC11 mRNA and protein levels were enhanced by DEX (dexamethasone) and by PROG (progesterone) in MCF7 (progesterone receptor-(PR-) positive) but not in MDA-MB-231 (PR-negative) breast cancer cells. This suggested a PR-signaling pathway involvement in ABCC11 regulation. Nevertheless, pregnenolone-16α-carbonitrile (GR antagonist) and clotrimazole strongly and moderately decreased ABCC11 expression levels in Glucocortocoid Receptor-(GR-) and Pregnane X Receptor (PXR)-positive MCF7 cells but not in MDA-MB-231 cells (GR- and PXR-positive). Thus, GR-signaling pathway involvement could not be excluded in ABCC11 regulation in MCF7 cells. Furthermore, ABCC11 levels were positively correlated with the PR status of postmenopausal patient breast tumors from two independent cohorts. Thus, in the subclass of breast tumors (Estrogen Receptor-(ER-) negative/PR-positive), the elevated expression level of ABCC11 may alter the sensitivity to ABCC11 anticancer substrates, especially under treatment combinations with DEX.